Tax and Brexit - Freedman, J (Oxford University Press, 2017)
It has been suggested that Brexit creates opportunities for the UK to become a tax haven with low rates of tax and new tax incentives. The opportunities created should not be exaggerated. On the one hand, some of the actions now being mooted, such as the further reduction of corporation tax, could have been taken regardless of the decision to leave the EU. On the other hand, the UK has played a leading role in formulating the OECD’s action points to combat base erosion and profit shifting (BEPS). Moving too far away from this programme would be contrary to stated government policy to counteract aggressive tax avoidance and would be seen as reneging on agreements with the global tax community. The UK’s extensive network of bi-lateral double taxation agreements could be placed in jeopardy by changes seen to be out of line with international norms, nor would such changes be conducive to the making of new international trade agreements. Most forms of Brexit would remove some constraints on the making of tax policy in the UK, enabling the government to introduce new exemptions and reliefs without the restrictions currently imposed by VAT directives, the requirement to satisfy the four freedoms, or the state aid regime. But this removal of restrictions on the freedom to make tax policy could lead to a temptation to respond to pressure groups and make rapid changes to the tax system that might well turn out to be ill-advised. Brexit offers some opportunities but also dangers. Any tax changes made need to be part of long-term and principled planning for the tax system as a whole, and tax incentives and reliefs should not be seen as quick fixes.